Kepastian Hukum Pelaksanaan Permenkes Nomor 14 Tahun 2021 terhadap Perpanjangan Izin Apotek - kristy anita; Heru Kuswanto (Universitas Merdeka Madiun, 2022)
One of the national goals of the State of Indonesia is to improve people's living standards, including in the health sector which is closely related to medicine. The management and distribution of drugs is strictly monitored by the government and can only be done at Pharmaceutical Service Facilities, one of which is a pharmacy. In The Minister of Health Regulation Number 14 of 2021 it is regulated that pharmacies can be operated by individual or non-individual business actors in the form of legal entities. This study wants to examine the implementation of The Minister of Health Regulation Number 14 of 2021 on the extension of pharmacy licenses. This study uses a legal research method with a statutory and conceptual approach. From the results of the study, it was found that the rules regarding the licensing of these pharmacies have been specifically regulated and the existing laws and regulations are coherent, but has not provided legal certainty for pharmacy business actors. The Minister of Health Regulation Number 14 of 2021 causes difficulties for business actors and the current OSS system is still unable to accommodate the needs of business actors.